2008
DOI: 10.1111/j.1365-3024.2008.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune responses to recombinant Plasmodium vivax tryptophan‐rich antigen (PvTRAg) among individuals exposed to vivax malaria

Abstract: Plasmodium vivax, the most widespread species of human malaria parasite responsible for 70-80 million cases each year requires a vaccine. In recent years, many potential vaccine candidate antigens have been identified from P. vivax including PvTRAg. We describe here cellular immune response to recombinant PvTRAg expressed in Escherichia coli. The in vitro stimulation of PBMCs derived from P. vivax-exposed individuals (n = 16) showed strong proliferative response (SI > 2.2) to PvTRAg as compared to PBMCs from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…These Plasmodium vivax tryptophan-rich proteins are expressed during blood stages of the parasite [24][27], [29]. Some of them, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These Plasmodium vivax tryptophan-rich proteins are expressed during blood stages of the parasite [24][27], [29]. Some of them, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Expression and purification of some of these PvTRAgs have previously been described [24], [26], [28][30]. Remaining PvTRAgs were cloned and expressed using the methods described elsewhere [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptophan‐rich proteins of P. vivax belong to ‘Pv‐fam‐a’ family and there is a stage‐specific expression of these proteins in the parasite, probably to perform different functions . Previously, we immunobiologically characterized large numbers of these proteins and hypothesized that some of them may be involved in red cell invasion . These proteins have exceptionally high tryptophan contents and the tryptophan residues are positionally conserved with a certain spatial pattern.…”
mentioning
confidence: 99%
“…These proteins need to be characterized so as to develop them as the drug or vaccine targets. Recently, we have described immunological characterization of some of these P.vivax proteins and reported that they were highly immunogenic in humans [10], [11], [12], [13], [14]. The tryptophan-rich domains of all these proteins were also conserved in the parasite population.…”
Section: Introductionmentioning
confidence: 99%